The Influence of Brand Image, Trust, and Online Customer Review on Snack Tray Purchase Decisions at the Haus Indonesia Brand - Weni, Chintya Ayu Panglipur; Surianto, Moh Agung (Majapahit Journal of Islamic Finance and Management, 2025)
The purpose of this study was to analyze the influence of Brand Image, trust, and online customer review variables on purchasing decisions for Snack Tray products on the Haus Indonesia brand, both partially and simultaneously. The study population included consumers who had purchased and consumed Haus Indonesia products at least once in the Gresik area, with a sample of 150 respondents selected through accidental sampling return techniques. Data analysis was carried out using quantitative methods through validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, F test, t test, and coefficient of determination. This study concluded that brand image, trust, and online customers partially had a positive and significant effect on purchasing decisions.